Pengaruh Pelatihan Kewirausahaan terhadap Kinerja UMKM Binaan Dinas Koperasi dan UKM Provinsi Jambi di Kota Jambi - Dewi Melati; Novita Ekasari; Dessy Elliyana (Jurnal Manajemen Kewirausahaan dan Teknologi, 2026)
This study to analyze the effect of Enterprenuership Training on the Performance of MSMEs fostered by the Jambi Provincial Cooperatives and SMEs Office. The 2025 training program focuses on the culinary sector, but its effectiveness in improving business performance has not been empirically measured. This study uses a quantitative approach by distributing questionnaires to 109 culinary MSMEs who participated in the training. The Entrepreneurship Training variable is measured through six dimensions, while MSME Performance through three dimensions. Data analysis was performed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results show that all variable indicators meet validity and reliability, with outer loading values ​​>0.7 and Composite Reliability >0.94. The R-Square value of 0.910 indicates that Entrepreneurship Training is able to explain 91% of the variation in MSME Performance. The hypothesis test yielded a path coefficient of 0.954 with a t-statistic of 56.97 and a p-value of 0.000, thus proving that Entrepreneurship Training has a positive and significant effect on MSME performance. This finding emphasizes that the quality of material delivery, trainer competence, and the relevance of training content contribute to increased sales, customer growth, and product competitiveness based on participant perceptions. This study emphasizes the importance of training as a strategy for strengthening MSMEs, although its scope is limited to culinary entrepreneurs. Further research is recommended to include other variables such as business experience, capital, and digital capabilities to understand the factors that influence MSME performance.